Technical Perspective: Software and Hardware Support for Deterministic Replay of Parallel Programs. - Jouppi, Norman P. (Communications of the ACM, 2009)
The article discusses another article in the issue, "Two Hardware-Based Approaches for Deterministic Multiprocessor Replay," by Derek R. Hower, Pablo Montesinos, Luis Ceze, Mark D. Hill, and Josep Torrellas, which examines hardware and software support and the challenges faced with the deterministic replay of parallel computer programs.